2011
DOI: 10.1002/ajh.22038
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prognostic factors for plerixafor‐based hematopoietic stem cell mobilization

Abstract: The introduction of plerixafor has enabled successful collection of stem cells in the majority of patients with lymphoma or myeloma in whom previous attempts at mobilization have failed. However, a proportion of patients have been shown to be resistant to this mobilization regimen. To identify the factors that impair stem cell mobilization and collection with plerixafor, we reviewed the data for 197 patients who had undergone mobilization with plerixafor and granulocyte-colony stimulating factor in Central Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…A recent study on identifying prognostic factors for prescribing plerixafor-based PBSC mobilization showed that an age of 65 years, a diagnosis of non-Hodgkin's lymphoma, and treatment with four chemotherapy regimens were significantly associated with mobilization failure. Given the congruence between these prognostic factors and GITMO criteria of 'predicted poor mobilizers', it is evident that PBSC mobilization is impacted by the existence of risk factors and hence, the early use of plerixafor for high-risk groups should be carefully considered [5]. Further study is warranted to prevent mobilization failure by maximizing the benefit of plerixafor in Korean clinical setting.…”
mentioning
confidence: 99%
“…A recent study on identifying prognostic factors for prescribing plerixafor-based PBSC mobilization showed that an age of 65 years, a diagnosis of non-Hodgkin's lymphoma, and treatment with four chemotherapy regimens were significantly associated with mobilization failure. Given the congruence between these prognostic factors and GITMO criteria of 'predicted poor mobilizers', it is evident that PBSC mobilization is impacted by the existence of risk factors and hence, the early use of plerixafor for high-risk groups should be carefully considered [5]. Further study is warranted to prevent mobilization failure by maximizing the benefit of plerixafor in Korean clinical setting.…”
mentioning
confidence: 99%
“…33 HSC mobilisation may be affected by: age, ethnicity, type and dose of cytokines used, the patient's diagnosis, number and type of previous chemotherapy cycles or radiation, and interval from last chemotherapy cycle. [33][34][35][36][37][38][39][40] However, these findings are not consistent across all studies and it is difficult to predict how individual patients will respond. Peripheral blood CD34 + cell counts correlate with numbers of CD34 + cells collected.…”
Section: What Is the Outcome Of Mobilisation?mentioning
confidence: 99%
“…Various patient-related and disease-related characteristics have been identified as having a negative impact on mobilization success rates. These include advanced age [25][26][27]; diagnosis of NHL [25]; prior radiation therapy, extensive prior chemotherapy, or prior treatment with lenalidomide or purine analogs [26][27][28][29][30][31][32][33][34][35][36][37][38]; a hypocellular marrow, marrow involvement at diagnosis, low platelet count, and refractory disease [25]; and prior mobilization failure. Historical failure rates with traditional mobilization approaches have been reported to be as high as 18% to 38% [18,[39][40][41][42], although more recent studies consistently show mobilization failure rates to be below 15% in patients with up-frontetreated MM [43][44][45] and below 10% when CM is incorporated into planned chemotherapy cycles for patients with NHL [46][47][48].…”
Section: Costs Associated With Poor Mobilization/failure To Mobilizementioning
confidence: 99%